Nebula-Relay Hypothesis: The Chirality of Biological Molecules in Molecular Clouds - Feng, Lei (Frontiers in Astronomy and Space Sciences, 2022)
The chiral puzzle of biological molecules is thought to be closely related to the origin of life and is still a mystery so far. Previously, we proposed a new model on the origin of life, Nebula-Relay hypothesis, which assumed that the life on Earth originated at the planetary system of the sun's predecessor star and then filled in the pre-solar nebula after its death. As primitive lives existed in the pre-solar nebula for a long time, did the chiral biomolecules form during this period? We explore such a possibility in this work and find that the ultra-low temperature environment of molecular cloud is beneficial to generate the chiral polymer chain of biological molecules.